(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose: The purpose of the study is to determine the factors influenced on consumers’ perceived risk and online customer purchasing behavior Design/Methodology/Approach: The primary quantitative method has been chosen to complete the study along with the survey procedure. Findings: It has been observed from the study that consumer perceived risks are associated with products’ prices, quality, and lack of information which lower the online purchases. Research, practical work, and social implication: The study helps to enlighten the factors that are integrated with consumers’ perceived risk and helps to enhance the online purchasing. Originality/ Value: The value of the study is that it provides a better understanding on the components that controls the consumers’ perceived risk.